Bisexuality in Bohemian Rhapsody: A Queer Study - Syabilla Maylya -; Mamik Tri Wedawati (Faculty of Language and Literature, University of Surakarta, 2022)
This research was meant to describe the shape of sexuality in Bryan Singer's